2018
DOI: 10.1177/0391560318810197
|View full text |Cite
|
Sign up to set email alerts
|

Keratinizing squamous metaplasia of the bladder: Our experience and current approaches

Abstract: Introduction: Bladder mucosa is anatomically covered by urothelial epithelium. The replacement of the urothelium with stratified squamous cells is defined as squamous metaplasia which can be keratinizing or non-keratinizing. Clinically, it is also known as leukoplakia or keratinizing cystitis of the bladder. Although several etiologic factors have been proposed such as chronic inflammation, irritative stimuli and infection, its pathogenesis is not clearly understood. The natural history of squamous metaplasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Although the fundamental aim of conservative TUR is to eradicate the risk of bladder squamous cancer development, the role of relieving urinary symptoms has also been observed. Benelli et al not only noted the regression of whitish plaque but also found resolution of severe LUTS by repeated TUR . A retrospective study further demonstrated the efficacy of laser surgery in relieving urinary symptoms by destroying bladder metaplasia lesion, with 68% of the 28 patients achieving at least 75% improvement in urinary symptoms at a mean follow‐up duration of 49 months .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the fundamental aim of conservative TUR is to eradicate the risk of bladder squamous cancer development, the role of relieving urinary symptoms has also been observed. Benelli et al not only noted the regression of whitish plaque but also found resolution of severe LUTS by repeated TUR . A retrospective study further demonstrated the efficacy of laser surgery in relieving urinary symptoms by destroying bladder metaplasia lesion, with 68% of the 28 patients achieving at least 75% improvement in urinary symptoms at a mean follow‐up duration of 49 months .…”
Section: Discussionmentioning
confidence: 95%
“…New treatments are being explored. Benelli et al successfully treated a KSM patient with severe LUTS by repeated TUR combined with intravesical instillation of hyaluronic acid . Guo et al found increased epidermal growth factor receptor (EGFR) expression in bladder KSM lesions, suggesting that EGFR may be a candidate treatment target …”
Section: Discussionmentioning
confidence: 99%
“…Considering the very low complication rate, our study supports transurethral resection as an alternative treatment for patients who are resistant to medical therapy [ 6 ]. Recently, Benelli et al [ 7 ] manage a man affected by LV with hyaluronic acid instillations with resolution of clinical symptoms. It could be considered the starting point and the gold standard in the follow-up of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…It could be considered the starting point and the gold standard in the follow-up of our patient. However, at present, further studies are required to formulate an adequate policy for therapeutic management of this unusual lesion of the bladder mucosa [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, squamous metaplasia is generally considered as preneoplastic and can develop into squamous carcinoma. 13,14 If bladder FEPs are accompanied by cancer, most researchers recommend further radical cystectomy. 15,16…”
Section: Discussionmentioning
confidence: 99%